Jesus’s Prayer Location in the Gospels and African Christianity - Ottuh, John (Stellenbosch Theological Journal, 2026)
Within Jesus’s involvement in prayers especially as it relates to locations, we are being confronted with the task of going through the records of the Gospels to find out how Jesus prayed in sacred spaces. Therefore, this essay examines Jesus’s prayer locations in the Gospels in comparison with modern African Christianity. Particularly, it intends to re-examine the concept and emphasis on a particular location for prayer called mountain and the issue of stipulated prayer duration. Using the comparative approach in African biblical criticism by drawing from Jesus’s location and pattern of private prayers in the Gospels, I argue that similarity, and theological nuances exist between biblical and African understanding of using mountain as a sacred space for prayer. Did Jesus pray in one particular location? Did Jesus stipulate particular duration for prayer?